FACTORS OF FORMATION OF ETHNIC SOLIDARITY - A. Bakanach (Вестник университета)
The study of ethnic solidarity is today a keen interest of scientists in various fields. This article examines the factors that contribute to the formation of inter-ethnic solidarity, problems and necessary conditions for solidarity. The factors related to the formation of ethnic solidarity, the author distinguishes: inter-ethnic solidarity, external environmental factors, internal environmental factors, personal factors.